2016
DOI: 10.1038/nsmb.3230
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of extracellular ion exchange and binding-site occlusion in a sodium/calcium exchanger

Abstract: Na+/Ca2+ exchangers utilize the Na+ electrochemical gradient across the plasma membrane to extrude intracellular Ca2+, and play a central role in Ca2+ homeostasis. Here, we elucidate their mechanisms of extracellular ion recognition and exchange through a structural analysis of the exchanger from Methanococcus jannaschii (NCX_Mj) bound to Na+, Ca2+ or Sr2+ in various occupancies and in an apo state. This analysis defines the binding mode and relative affinity of these ions, establishes the structural basis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
166
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(210 citation statements)
references
References 58 publications
23
166
1
1
Order By: Relevance
“…Recently, a thorough structural analysis of ion recognition in the outward-facing state was performed by soaking NCX_Mj crystals in solutions with different ionic compositions [27]. These studies unequivocally confirm the model derived from the molecular dynamics and the ion-flux assays mentioned above.…”
Section: Structure-functional Assignments Of Four Binding Sites Insupporting
confidence: 56%
See 4 more Smart Citations
“…Recently, a thorough structural analysis of ion recognition in the outward-facing state was performed by soaking NCX_Mj crystals in solutions with different ionic compositions [27]. These studies unequivocally confirm the model derived from the molecular dynamics and the ion-flux assays mentioned above.…”
Section: Structure-functional Assignments Of Four Binding Sites Insupporting
confidence: 56%
“…However, only recently has a major advancement in understanding the structural basis for this mechanism been achieved by solving the crystal structure of NCX_Mj from the arachaeabacterium Methanococcus jannaschii [24]. In combination with known crystal structures, specially designed MD simulations and extended kinetic analyses of ion-fluxes in mutants revealed that the simultaneous occupation of 3Na + and 1Ca 2+ is thermodynamically forbidden [25,26,27]. Similarly to mammalian NCX, the NCX_Mj protein also translocates Na + and Ca 2+ with a stoichiometry of 3:1, although in contrast with NCX_Mj, the three mammalian genes NCX1-3 contain a large cytosolic regulatory loop (~520 aa) between helices 5 and 6 [28,29,30].…”
Section: X-ray Structure Of Archaeal Ncx Reveals the Architecture mentioning
confidence: 99%
See 3 more Smart Citations